PENGARUH BRAND COMPETENCE, CREDIBILITY DAN SATISFACTION TERHADAP WORD OF MOUTH BEHAVIOR MELALUI TRUST - Adiati Hardjanti (Universitas Trisakti, 2009)
The purpose of this study is to examine whether there are exists the influence Brand Competence, Brand Credibility and Brand Satisfaction towards Corporate Brand Trust will influence of Purchase Intention and WOM Behavior.Data collected by distributing questionnaires to 120 respondents who used Nokia handphone product. This research used purposive sampling technique and overall of hypotheses tested by structural equation modeling using Amos 7.0 program.The result showed some variables not support for hypotheses, which is Brand Competence and Satisfaction has positive effect to brand trust. Corporate Brand Trust has positive effect to Current Purchase Intention. Brand credibility has negative effect to brand trust and brand trust has negative effect to purchase intention for product innovation. Corporate Brand Trust has negative effect to WOM Behavior. Corporate Brand Trust has positive effect but not significant to Intention for Product Innovation and Current Purchase Intention.Keywords : Brand competence, Brand credibility, Brand Satisfaction, Corporate brand trust, Purchase intention, Word of mouth